Inovasi Ekonomi Kreatif Dalam Pengembangan Wisata Religi Berbasis Pesantren : Studi Kasus Di Desa Ciomas Pesantren Sirnarasa Kecamatan Panjalu Dan Desa Jelat Pesantren Banyulana Kecamatan Baregbeg Kabupaten Ciamis - Ayu Lestarini; Syuhudul Anwar (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2023)
Creative economic innovations are developing in two villages in Ciamis Regency, namely Ciomas Village, Panjalu District and Jelat Village, Baregbeg District, where there are Islamic boarding schools and religious tourism activities. Data collection techniques are observation, interviews, documentation, and literature studies. Data analysis techniques namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study show that it is true that there are creative economic innovations that are useful in the development of religious tourism in the two villages. In overcoming the perceived obstacles, the Village Government and Islamic Boarding School have made various efforts to overcome them at this time. As for those that have not been implemented, they are still due to deficiencies in one way or another in their implementation. There are two differences between the two villages that can be seen after conducting research, namely for Ciomas Village, the Village Government has not yet had a creative economy initiative that supports religious tourism but is willing to work together to help and succeed in innovation programs with residents and Islamic boarding schools. As for Jelat Village, the village government also has a program for the development of religious tourism in the area, but the enthusiastic residents are passive.